A QUANTITATIVE EVALUATION OF BOND STRENGTH BETWEEN COARSE AGGREGATE AND CEMENT MORTAR IN CONCRETE - Al-Attar, Tareq S. (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿﻿The hardened concrete could be considered as a three-phase composite material consisting of cement paste, aggregate and interface zone between them. The bond between cement paste and aggregate depends largely on the interface zone characteristics. Most methods and specimens used to measure bond strength between aggregate and cement paste are not standardized and could be only described as a gross simplification of the real situation around interfaces. The present work represents a proposed quantitative evaluation for the bond strength that depends mainly on the results of the uniaxial compression test of concrete which is a simple and standardized test. The used coarse aggregate was intentionally treated with engine oil and with oil paint to investigate the effect of these coatings on bond strength. The effectiveness of surface coating by engine oil or paint was tested through the comparison of water absorption for coarse aggregate before and after the treatment. Both methods were highly successful in preventing water ingress inside aggregate particles. The experimental program included absorption for coarse aggregate, and slump, compressive strength, and splitting tensile strength tests for concrete. The program for strength tests was extended to the age of 180 days. The results of the present work showed that the estimated bond strength at any time ranged from (6.1 - 8.4) percent of the compressive strength for the investigated concrete. It was concluded that the values of bond to splitting tensile strength ratio could be considered as an indication to weather the failure of concrete is occurred due to bond lose or because the stresses at the interface zone had exceeded the tensile strength.